Effects of tensile strain in barrier on optical gain spectra of GaInNAs/GaAsN quantum wells - Fan, Weijun (2013)
The band structures, optical gain spectra, and transparency radiative current densities of compressive-strained GaInNAs quantum wells(QWs) with different tensile-strained GaAsN (N composition from 0 to 3%) barriers are systematically investigated using a modified 6x6 k.p Hamiltonian including the heavy hole, light hole, and spin-orbit splitting bands. We found that the transition energy decreases when increasing the N composition in the barrier. The optical gain spectra and maximum optical gain as a function of carrier density and radiative current density are obtained for the GaInNAs/GaAsN QWs with well width of 5 nm, Inw = 28%, and Nw= 2.66% emitting around 1.55 μm. The transparency carrier density increases with the nitrogen composition in the GaAsN barrier. The transparency radiative current density decreases with more nitrogen being added into the barrier, which is in agreement with the recent experimental observation.